DAMPAK KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KINERJA KARYAWAN: STUDI KASUS PERUSAHAAN START-UP DI PT. GLOBAL TALENTLYTICA INDONESIA - Krishnabudi, Nyoman Gede; Saleh, Chairul; Purwanti, Gettik Andri; Natalia, Princessa (Bisma: Jurnal Bisnis dan Manajemen, 2023)
This study aims to examine and analyze the effect of compensation and work environment variables on employee job satisfaction partially. The population and sample in this study were 51 respondents who were all employees of PT. Global Talentlytica. This research is classified as explanatory research. Multiple linear regression analysis was applied as data analysis method. The results show that compensation and work environment have a positive and significant impact on employee job satisfaction partially. This indicates that the better the compensation and work environment provided by the PT. Global Talentlytica, the greater the job satisfaction of employees in the company. Compensation and work environment are crucial for companies in maintaining employee job satisfaction.